Glutathione Peroxidase1 Gene Polymorphism (GPx1 Pro198Leu) in Association with Blighted Ovum - Asiyeh Moshtaghi; Reyhaneh Sariri; Hamidreza Vaziri; Horiyeh Shayegan (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To evaluate salivary GPx-1 gene polymorphism in pregnant women suffering from blighted ovum. Method: In this case-control study, 34 blighted ovum patients and 34 healthy controls were studied. Genomic DNA was extracted from the saliva. The genotypes were determined by restriction fragment length polymorphism (RFLP-PCR) technique. Mad Calc (version 12.1) was used for statistical analysis. Result: The frequency of CC, CT, and TT genotypes of GPx-1 gene were 41%, 44% and 14%, respectively in blighted ovum patients and in healthy volunteers were 44%, 47%, and 8.82-9%, respectively. After statistical analysis, the study showed no significant association between this polymorphism and blighted ovum (with p = 0.63). Conclusion: These results indicated no significant association between GPx-1 (Pro198Leu) polymorphism and blighted ovum. However, further research is required to clarify the role of gene polymorphism in blighted ovum. [Indones J Obstet Gynecol 2016; 1: 15-18] Keywords: abortion, blighted ovum, glutathione peroxidase-1, GPx- 1, RFLP-PCR